Uso de coproduto siderúrgico do tipo pó proveniente do sistema de captura de particulados de escória de dessulfuração KR e cimento Portland para estabilização de solos orgânicos de baixa consistência - Nunes, Nathália Lemos (2024)
Research has been exploring alternatives to Portland cement to improve low consistency soils, aiming not only to stabilize the soils but also to offer environmental and economic benefits, such as the indirect reduction of CO¢ emissions. This study investigates the cementation of a soft organic soil by evaluating different cementing agents and curing periods, focusing on physical, mechanical, and chemical parameters. The analyzed soil is a low-consistency clay with 49% organic matter, collected in the northern region of EspÌrito Santo, Brazil. The cementing agents used were high early strength Portland cement and a steelmaking by-product, captured by a particulate dust collection system from KR slag, referred to as <KRP= in this study. The mixtures were prepared with additions of 15% and 30% of the cementing agents based on the total mass of dry soil. The evaluated parameters include moisture content, dry apparent specific gravity, liquid and plastic limits, unconfined and undrained compressive strength, consolidation tests, and microstructural analysis using XRD, SEM, and EDS. The results indicated that KRP is a viable and recommended alternative to Portland cement for this soil, especially at the 30% dosage, showing better performance in terms of mechanical strength and compressibility during consolidation. Portland cement, at the same dosage, did not show equivalent improvements in unconfined compressive strength, demonstrating a reduction in strength after 28 days of curing. However, the mixture showed the least variation in void ratio in the consolidation test. Both cementing agents caused changes in the pure soil, and XRD analyses indicated the formation of hydrated products responsible for the increase in mechanical strength